Organizational Structure as a Fundamental Function of Effective Management. The Case of Tesla (Global Journal of Management and Business Research, 2022)
Organizational structure is a construct that has had an important role in terms of the performance of an organization Therefore the effective management of an organization has been systematically and consistently linked with the deep understanding of the importance of the organizational structure and its proper design or its re-engineering The external organizational environment is at the present so fluid that decisions concerning structure and corporate restructuring have become central It has been emphasized that the structural decisions concerning the organizational structure are undoubtedly among the most important decisions undertaken by the leadership This can be justified as the organizational structure determines the ways in which overall work and tasks are formally divided grouped and proper ways of coordinating them are developed The structure therefore is not something simple It reflects the theory of each organization regarding the way it trusts that the various tasks within should be separated grouped in ways that can efficiency can be achieved
Keywords: organizational structure; performance; tesla; productivity; central management